La relevancia del acompañamiento psicosocial en la implementación de la interrupción voluntaria del embarazo en tres causales en Chile. - González Aristegui, Daniela; Montero, Adela; Ramírez-Pereira, Mirliana; Tapia de la Fuente, Belén; Robledo, Paz; Casas, Lidia C.; Vivaldi, Lieta (Revista Facultad Nacional de Salud Pública, 2024)
Objective: To describe and analyze the relevance of the psychosocial support team concerning services related to the voluntary interruption of pregnancy in public health institutions. Methodology: Qualitative, post-positivist design. Chain sampling, identifying psychosocial support professionals. Semi-structured interviews and content analysis were conducted. The methodological rigor criteria of transferability, dependability, credibility, auditability, and theoretical-methodological adequacy were met. Results: Information from 13 professionals from the country's psychosocial support team was included. Following an inductive process of open coding, the categories of Professional role; Motivation; Facilitators: and Obstacles to the performance of the psychosocial team emerged, and the Relevance of psychosocial support emerged as a meta-category. Conclusion: To measure the impact of incorporating psychosocial professionals in obstetric and gynecological units with different positions on the law requires an indepth approach. The accounts of those who perform this role allow us to analyze this process and propose strategies to facilitate their performance.